«Where once the Russian flag is raised, there it should not go down» - N. A. Shabelnikova (Омский научный вестник: Серия "Общество. История. Современность")
Natalya Alekseevna Shabelnikova, Doctor of Historical Sciences, Professor, Police Colonel, Honored Worker of Internal Affairs of the Russian Federation. She is the author of scientific research on the history of law enforcement agencies in a wide problem-thematic and chronological range. This interview was agreed in October 2022 during the scientific official journey N. A. Shabelnikova in Omsk to participate in the work of the II All-Russian Scientific and Practical Conference «Activities of domestic special services in the era of social cataclysms». The interview was given remotely, and then edited by Natalya Alekseevna from Vladivostok in January 2023. The conversation was devoted to the prospects for studying the history of Russian special services in Russia, modern estimates of the historiography of the Civil War in the Far East and the policy of preserving historical memory in Russia.